Pedagogical Negotiation in an Unequal Digital Ecosystem: A Case Study of Science Education in Higher Education - Ariansyah Ariansyah; Muhammad Roil Bilad; Sutarto Sutarto; Nova Kurnia; Kadir Alpan Alaydrus; Pathan Pathan; Irham Azmi; Sergii Sharov (Faculty of Engineering and Applied Science, 2025)
This study qualitatively investigates the dynamics of digital technology use in science education at the university level, aiming to fill a gap in the literature that predominantly emphasizes quantitative impacts over user experiences. Employing a case study design, data were collected from six lecturers and ten students in West Nusa Tenggara through in-depth interviews. The data were analyzed iteratively using a Grounded Theory approach to develop a theoretical explanation rooted in participants' lived experiences. The main finding of this study is a substantive theory: the Model of Pedagogical Negotiation in an Unequal Digital Ecosystem. This theory posits that the effectiveness of technology lies not in its sophistication but in the ability of lecturers and students to engage in “pedagogical negotiation” to overcome systemic barriers. Two key barriers were identified: (1) a multifaceted digital divide (infrastructural, economic, geographical), often “invisible” to institutions, and (2) institutional fragmentation caused by non-standardized platforms and a lack of coordination among lecturers, which creates a stressful and inefficient learning environment. In conclusion, optimizing digital technology in education requires a paradigm shift from merely providing tools toward building a supportive, inclusive, and human-centered learning ecosystem.